Distribution and Mineralogical Characteristic of Raya Volcanics, West Kalimantan - Draniswari, Windi Anarta; Pratiwi, Fadiah; Ngadenin; Sukadana, I Gde; Adimedha, Tyto Baskara; Ciputra, Roni Cahya; Argianto, Ekky Novia Stasia; Aminarthi, Erwina; Supraba, Vertika Dhianda (EKSPLORIUM, 2021)
There are several volcanic rocks in a radius of 150 km from where the Nuclear Power Plant (NPP) site project in West Kalimantan. The Mesozoic volcanic rocks have not been characterized for volcanic hazard evaluation purposes due to their old age. However, the distribution of Raya Volcanic Rocks that covers the site area and the wider area up to 150 kilometers from the site makes this rock group quite important to be characterized to find out how its activities in the past. This paper’s objective is to comprehend the distribution and characteristics of Raya Volcanic Rocks for NPP site volcanic hazard evaluation purposes. Fieldwork and lineament analyses were conducted to map and interpret the distribution of Raya Volcanic Rocks while mineralogical analysis using petrography and micro XRF were conducted to characterize the Raya Volcanic Rocks. The distribution of Raya Volcanic Rocks that relatively show NNW–SSE orientation is probably controlled by the NNW–SSE fault system. The analyses resulted that Raya Volcanic Rocks erupted as lava flows derived from mafic magma as a product of mantle partial melting that underwent crystal fractionation, injection of hotter/more Ca-rich magma, and magma mixing on an open-system magmatic process.